Investigation of the association of serum GFAP and NfL with brain and upper cervical MRI volumes in AQP4-IgG-positive NMOSD and MOGAD - Schindler, Patrick; Grittner, Ulrike; Rust, Rebekka; Asseyer, Susanna; Bellmann-Strobl, Judith; Schmitz-Hübsch, Tanja; Scheel, Michael; Jarius, Sven; Wildemann, Brigitte; Reindl, Markus; Benkert, Pascal; Kuhle, Jens; et al. (Therapeutic advances in neurological disorders, 2025)
Background: Serum glial fibrillary acidic protein (sGFAP) is associated with disease activity in aquaporin-4-immunoglobulin G-seropositive neuromyelitis optica spectrum disorders (AQP4-IgG+NMOSD). Serum neurofilament light chain (sNfL) is a biomarker for neuroaxonal damage. However, the association of sGFAP and sNfL with magnetic resonance imaging (MRI) volumes in AQP4-IgG+NMOSD is unclear. - Objectives: To investigate the associations of sGFAP and sNfL with brain MRI volumes in AQP4-IgG+NMOSD. - Design: Monocentric, retrospective, observational study. - Methods: In 33 clinically stable patients with AQP4-IgG+NMOSD, 17 patients with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), and 15 healthy controls (HC), sGFAP and sNfL were measured at 2 (HC = 1) and 3-Tesla MRIs were obtained at 4 (HC = 1) yearly visits. Associations between biomarkers and MRI metrics were evaluated using linear models. - Results: In AQP4-IgG+NMOSD, but not in MOGAD and HC, higher sGFAP was associated with lower hippocampus (β = −2.0 (95% confidence interval: −3.4, −0.7), p = 0.004) and thalamus volumes (β = −2.5 (−4.3, −0.7), p = 0.006) and higher MRI cerebrospinal fluid volume (β = 1.8 (0.7, 3.2), p = 0.01), and, statistically less robust, with lower whole brain (β = −2.3 (−5.3, 0.8), p = 0.15) and gray matter volumes (β = −1.8 (−4.0, 0.4), p = 0.10). Furthermore, higher sGFAP (β = −0.06 (−0.11, −0.002), p = 0.04), but not sNfL (β = −0.02 (−0.08, 0.03), p = 0.38), was associated with percent brain volume change in AQP4-IgG+NMOSD. - Conclusion: The specific associations of sGFAP with brain MRI volumes corroborate sGFAP as a biomarker for disease activity in AQP4-IgG+NMOSD.